2016
DOI: 10.1101/040113
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exploiting single-cell quantitative data to map genetic variants having probabilistic effects

Abstract: Despite the recent progress in sequencing technologies, genome-wide association studies (GWAS) remain limited by a statistical-power issue: many polymorphisms contribute little to common trait variation and therefore escape detection. The small contribution sometimes corresponds to incomplete penetrance, which may result from probabilistic effects on molecular regulations. In such cases, genetic mapping may benefit from the wealth of data produced by single-cell technologies. We present here the development of… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 64 publications
0
16
0
Order By: Relevance
“…Single‐cell molecular expression profiling of isogenic cells demonstrated that noise in gene expression (refered as the stochastic variation of mRNA abundance) is subjected to genetic control, and reproducible differences in noise were reported between divergent genetic backgrounds (Ansel et al ., ; Chuffart et al ., ; Fehrmann et al ., ). In this sense, recent advances in the field are able to predict, localize and validate single SNPs affecting a trait (Chuffart et al ., ). Given the differences owing to environmental perturbations even between cells within isogenic cultures, advances in single‐cell technologies could be greatly exploited to help understand the consequences of noise and natural expression variation.…”
Section: Expression Divergence: Cis–trans Factorsmentioning
confidence: 97%
See 1 more Smart Citation
“…Single‐cell molecular expression profiling of isogenic cells demonstrated that noise in gene expression (refered as the stochastic variation of mRNA abundance) is subjected to genetic control, and reproducible differences in noise were reported between divergent genetic backgrounds (Ansel et al ., ; Chuffart et al ., ; Fehrmann et al ., ). In this sense, recent advances in the field are able to predict, localize and validate single SNPs affecting a trait (Chuffart et al ., ). Given the differences owing to environmental perturbations even between cells within isogenic cultures, advances in single‐cell technologies could be greatly exploited to help understand the consequences of noise and natural expression variation.…”
Section: Expression Divergence: Cis–trans Factorsmentioning
confidence: 97%
“…Moreover, environmental conditions may not be the sole source of fluctuations in gene expression. Single‐cell molecular expression profiling of isogenic cells demonstrated that noise in gene expression (refered as the stochastic variation of mRNA abundance) is subjected to genetic control, and reproducible differences in noise were reported between divergent genetic backgrounds (Ansel et al ., ; Chuffart et al ., ; Fehrmann et al ., ). In this sense, recent advances in the field are able to predict, localize and validate single SNPs affecting a trait (Chuffart et al ., ).…”
Section: Expression Divergence: Cis–trans Factorsmentioning
confidence: 99%
“…1). All strains of the panel also harboured a P GAL1 -GFP reporter of network activity, where the promoter of the GAL1 gene controlled the expression of a GFP fluorescent protein destabilized by a degradation signal 27,28 . GAL1 is a paralogous gene of GAL3 29 and transcription at its promoter is commonly used as a proxy of GAL network activity 15,20,22 .…”
Section: Resultsmentioning
confidence: 99%
“…We previously described a statistical method (ptlmapper) that can use the full distribution of single-cell traits to specifically identify scPTL 7 . This method looks for scPTL that may affect any property of the single-cell expression distribution, and not only specific pre-defined features such as mean, variability or dispersion.…”
Section: Discussionmentioning
confidence: 99%
“…it has a probabilistic effect, but only apparently because, although they are not known, compensatory deterministic factors exist. In addition, using model organisms and single-cell measurements, we and others have shown that genetic variants can also have effects that are inherently probabilistic: even in a controlled context, mutations can sometimes affect only some cells or individuals [1][2][3][4][5][6][7] . Consequently, we previously introduced the concept of single-cell Probabilistic Trait Loci (scPTL) 8 .…”
Section: Introductionmentioning
confidence: 99%